Alkali-free oxide glass substrate for chip packaging, preparation method and application thereof
Patent Information
- Application Number
- CN202611144936.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有封装玻璃基板存在增韧导致介电损耗升高、低损耗配方脆性突出、热膨胀系数难以精准调控的问题,本发明提供一种低脆性、高韧性、低热膨胀系数、低介电损耗的芯片封装用无碱氧化物玻璃基板、制备方法及应用,其通过“复合二价金属氧化物+低极化稀土氧化物+复合微量助剂”的多组分协同改性,通过引入小离子半径的 Sc2O3与 Y2O3、La2O3形成多尺度网络空隙填充,同时引入 ZnO 降低高温黏度,以 Sc2O3的高场强补强抵消ZnO 的网络稀释作用,实现了高韧性、低损耗与优良成型性的统一,最终实现一种同步满足CTE=(4~6)×10-6/℃、KIC≥1.2 MPa·m1/2、20 GHz tanδ<0.0045的无碱氧化物玻璃基板,适配高算力、高频、光电封装等先进场景
本发明通过“大-中-小”稀土离子的多尺度网络间隙填充效应,以 Sc3+高场强补强作用抵消 ZnO 的网络稀释效应,并借助 ZrO2和SnO2协同作用抑制界面极化与微析晶,从机理上破解了封装玻璃“增韧-低损耗-低膨胀”三角矛盾。所得玻璃基板 25~300℃平均线热膨胀系数 CTE为 4.0~6.0×10-6/℃,与硅芯片精准匹配;断裂韧性 KIC 1.2~1.5MPa·m1/2;20 GHz@25℃介电损耗 tanδ<0.0045,且无碱离子迁移风险,高温绝缘稳定性优良。制备工艺兼容溢流下拉法、狭缝下拉法、浮法等主流量产方法,可广泛应用于高算力 AI 芯片、HBM 中介层、6G 毫米波射频芯片、共封装光学(CPO)及 TGV 垂直互连等先进封装场景,产业化前景广阔。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of packaging substrate technology, specifically to an alkali-free oxide glass substrate for chip packaging with low brittleness, high toughness, low coefficient of thermal expansion, and low dielectric loss, its preparation method, and its application. It can be applied to glass substrates for glass through-hole (TGV) packaging of high-performance AI chips, high-bandwidth memory (HBM), and 6G millimeter-wave radio frequency chips. Background Technology
[0002] 5G millimeter wave, 6G terahertz radio frequency, high-performance GPU / AI chips, and high-bandwidth memory HBM place three stringent requirements on packaging substrates: extremely low high-frequency dielectric loss (20 GHz tanδ < 0.005), and a low coefficient of thermal expansion matching silicon (CTE = 4 × 10⁻⁶). -6 / ℃~6×10 -6 / ℃), high crack resistance (K IC ≥1.2 MPa·m 1 / 2 ).
[0003] The existing materials and their shortcomings are as follows: 1. Organic resin substrate: CTE generally > 12 × 10 -6 / ℃, 20GHz loss >0.008 (e.g., FR-4 substrate), prone to deformation and delamination at high temperatures; 2. Commercial alkali-free display glass (such as LCD substrate glass): K IC Only 0.9–1.1 MPa·m 1 / 2 Laser drilling is prone to edge chipping, and tanδ > 0.005 at 20 GHz; 3. Commercial alkali aluminosilicate cover glass (such as mobile phone screen protection glass): contains 3~15wt% alkali metal oxides, CTE=(7~9)×10 -6 At ℃, 20 GHz tanδ>0.01, there is a risk of alkali ion migration, which cannot meet the requirements of high-end packaging.
[0004] Current technologies cannot simultaneously achieve a thermal expansion coefficient CTE of (4~6)×10 -6 / ℃、K IC ≥1.2 MPa·m 1 / 2 The synergistic balance between 20GHz tanδ<0.0045 and the absence of alkali metal oxides has become a technical bottleneck in advanced chip packaging. Summary of the Invention
[0005] To address the problems of increased dielectric loss due to toughening in existing packaging glass substrates, brittleness in low-loss formulations, and difficulty in precisely controlling the coefficient of thermal expansion, this invention provides a low-brittleness, high-toughness, low coefficient of thermal expansion, and low-dielectric-loss alkali-free oxide glass substrate for chip packaging, its preparation method, and its application. This substrate achieves a multi-component synergistic modification through "composite divalent metal oxide + low-polarity rare earth oxide + composite trace additives." By introducing Sc2O3 with a small ionic radius to form a multi-scale network of voids with Y2O3 and La2O3, and simultaneously introducing ZnO to reduce high-temperature viscosity, the high field strength of Sc2O3 counteracts the network dilution effect of ZnO, achieving a balance between high toughness, low loss, and excellent formability. Ultimately, it achieves a substrate that simultaneously satisfies CTE = (4~6) × 10⁻⁶. -6 / ℃、K IC ≥1.2 MPa·m 1 / 2 An alkali-free oxide glass substrate with tanδ < 0.0045 at 20 GHz is suitable for advanced applications such as high computing power, high frequency, and optoelectronic packaging.
[0006] This invention discloses an alkali-free oxide glass substrate for chip packaging. The glass substrate is completely free of alkali metal oxides Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O, and also free of BaO and variable-valence rare earth oxides Ce₂O₃, Nd₂O₃, and Pr₂O₃. The total amount of each component is 100% by molar percentage, and it is composed of the following components: SiO2 55.0~65.0 mol% Al₂O₃ 12.0–18.0 mol% B2O3 8.0~15.0 mol% Complex divalent metal oxides RO 6.0–12.0 mol% Rare earth modified oxide Re₂O₃ 1.5–4.5 mol% The compound trace additive RO2 content is 0.5–1.2 mol%; in: The composite divalent metal oxide RO is composed of MgO, ZnO, CaO, and SrO, with MgO accounting for 40% to 60% of the total molar amount of RO. The rare earth modified oxide Re2O3 contains Sc2O3, and the rare earth modified oxide Re2O3 also contains at least one of Y2O3 and La2O3, wherein 0.1 mol% ≤ Sc2O3 ≤ 0.5 mol%, Y2O3 ≤ 2.8 mol%, and La2O3 ≤ 3.0 mol%; The composite trace additive RO2 contains both ZrO2 and SnO2, with a molar ratio of 4:6 to 7:3.
[0007] As a further improvement of the present invention, the content of each component, in molar percentage, is as follows: SiO2 58.0~62.0 mol% Al₂O₃ 14.0–16.0 mol% B₂O₃ 10.0–13.0 mol% RO 8.0~10.0 mol% Re₂O₃ 2.5–3.5 mol% RO20.5~1.0 mol%.
[0008] As a further improvement of the present invention, the content of each component in the RO satisfies the following: MgO 3.3-7.2 mol%, ZnO 0.5-1.8 mol%, CaO 1.0-2.4 mol%, SrO 1.0-2.0 mol%; and the molar ratio of ZnO to MgO is 0.13-0.25.
[0009] As a further improvement of the present invention, the molar ratio of Sc2O3 to (Y2O3+La2O3) in the Re2O3 is (0.03~0.50):1.
[0010] As a further improvement of the present invention, in the composite trace additive RO2, ZrO2 is 0.3-0.7 mol% and SnO2 is 0.2-0.6 mol%.
[0011] This invention also discloses a method for preparing the above-mentioned alkali-free oxide glass substrate for chip packaging, comprising the following steps: Step 1, Raw material pretreatment: Based on the composition of the glass substrate, select oxide or corresponding carbonate raw materials with a purity of ≥99.5%, convert them to mass ratios according to molar ratios, mix them evenly, and prepare the batch material. Step 2, High-temperature melting and clarification: The batch material is placed in a platinum container or a low-alkali refractory kiln with an alkali metal oxide content ≤0.1%, and kept at 1580~1650℃ for 6~8 h for melting and clarification; Step 3, Cooling and homogenization: Cool the clarified glass melt to 1420-1480℃ and homogenize it by mechanical stirring for 1-3 hours; Step 4, Glass Forming: The homogenized molten glass is formed using the overflow pull method, slit pull method, rolling method, float glass method or casting method to obtain a glass substrate blank or sheet with a thickness of less than 2.0 mm. Step 5, Annealing: The formed glass substrate blank or original sheet is annealed to 60~80℃ at a cooling rate of 10~350 ℃ / min to obtain an alkali-free oxide glass substrate for chip packaging.
[0012] The present invention also discloses an application of the above-mentioned alkali-free oxide glass substrate for chip packaging, wherein the glass substrate is applied to any one of the following: high computing power AI chip packaging substrate, high bandwidth memory (HBM) interposer, 6G millimeter wave RF chip packaging substrate, co-packaged optics (CPO) glass interposer, through glass via (TGV) vertical interconnect substrate, and glass-based fan-out packaging substrate.
[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes the multi-scale network gap-filling effect of "large-medium-small" rare earth ions to achieve Sc 3+ The high field strength reinforcement counteracts the network dilution effect of ZnO, and the synergistic effect of ZrO2 and SnO2 suppresses interfacial polarization and microcrystallization, thus fundamentally resolving the "toughening-low loss-low expansion" triangle contradiction in encapsulated glass. The average linear thermal expansion coefficient (CTE) of the resulting glass substrate at 25–300℃ is 4.0–6.0 × 10⁻⁶. -6 / ℃, precisely matched to silicon chips; fracture toughness KIC 1.2~1.5MPa·m 1 / 2 The dielectric loss tanδ < 0.0045 at 20 GHz @ 25℃, with no risk of alkali ion migration, and excellent high-temperature insulation stability. The fabrication process is compatible with mainstream mass production methods such as overflow pull-down, slot pull-down, and float glass, and can be widely applied to advanced packaging scenarios such as high-performance AI chips, HBM interposers, 6G millimeter-wave RF chips, co-packaged optics (CPO), and TGV vertical interconnects, showing broad industrialization prospects. Detailed Implementation
[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] This invention provides an alkali-free oxide glass substrate for chip packaging, its preparation method, and its application. It simultaneously meets three core indicators: thermal expansion, fracture toughness, and high-frequency dielectric loss, while also taking into account processing yield and high-temperature insulation stability. It is suitable for advanced chip packaging such as high computing power, millimeter-wave high frequency, optoelectronic packaging, and microelectromechanical systems.
[0016] The alkali-free oxide glass substrate for chip packaging of the present invention is completely free of alkali metal oxides Li2O, Na2O, K2O, Rb2O and Cs2O, and also free of BaO and variable-valence rare earth oxides Ce2O3, Nd2O3 and Pr2O3; the total amount of each component is 100% by molar percentage, and it is composed of the following components: SiO2 55.0–65.0 mol%, preferably 58.0–62.0 mol%; Al₂O₃ 12.0–18.0 mol%, preferably 14.0–16.0 mol%; B₂O₃ 8.0–15.0 mol%, preferably 10.0–13.0 mol%; The composite divalent metal oxide RO is 6.0–12.0 mol%, preferably 8.0–10.0 mol%; Rare earth modified oxide Re₂O₃ 1.5–4.5 mol%, preferably 2.5–3.5 mol%; The compound trace additive RO2 is 0.5–1.2 mol%, preferably 0.5–1 mol%; in: The composite divalent metal oxide RO is composed of MgO, ZnO, CaO, and SrO, with MgO accounting for 40% to 60% of the total molar amount of RO. Specifically, MgO accounts for 3.3 to 7.2 mol%, ZnO for 0.5 to 1.8 mol%, CaO for 1.0 to 2.4 mol%, and SrO for 1.0 to 2.0 mol%, and the molar ratio of ZnO to MgO is 0.13 to 0.25. The rare earth modified oxide Re2O3 contains Sc2O3, and the rare earth modified oxide Re2O3 also contains at least one of Y2O3 and La2O3, and the molar ratio of Sc2O3 to (Y2O3+La2O3) in Re2O3 is (0.03~0.50):1; The composite trace additive RO2 contains both ZrO2 and SnO2, with ZrO2 at 0.3~0.7 mol% and SnO2 at 0.2~0.6 mol%, and the molar ratio of the two is 4:6~7:3.
[0017] The glass substrate simultaneously meets the following performance indicators: (1) The average linear thermal expansion coefficient CTE in the range of 25 to 300℃ is 4×10 -6 / ℃~6×10 -6 / ℃; (2) Fracture toughness K IC The value is 1.2~1.5 MPa·m 1 / 2 ; (3) Under the test conditions of room temperature 25℃ and 20GHz, the dielectric loss tanδ<0.0045.
[0018] The mechanisms of action and synergistic relationships of various oxides are as follows: 1) SiO2 is a network forging body that constructs a low-polarization silicon-oxygen framework to ensure basic low-loss characteristics; when the content is less than 55 mol%, the glass network structure is loose, resulting in high-frequency relaxation polarization; when the content is higher than 65 mol%, the glass melt viscosity increases sharply and the toughness decreases, so the upper limit is locked at 65 mol%.
[0019] 2) Al2O3 is a network intermediate. The glass of this invention contains two structural units: [AlO4] and [AlO6]. [AlO4] crosslinks the silicon-oxygen network, passivates crack propagation channels, and improves fracture toughness K. IC A content exceeding 18 mol% introduces a significant dipole polarization effect, resulting in excessive high-frequency losses and a substantial increase in melting temperature, thus increasing the challenges of melting and manufacturing. A content below 12 mol% reduces the glass's strength and fracture toughness.
[0020] 3) B2O3 is a network forger. The glass of this invention contains two structural units: [BO3] and [BO4]. [BO3] has a planar structure and low polarization characteristics, which can offset the loss problem caused by the increase of Al2O3, while reducing the high-temperature melt viscosity and improving the glass forming process performance. When the content is less than 8 mol%, the loss is difficult to meet the limit requirement of 0.0045. When the content is higher than 15 mol%, the glass network is loose, the CTE increases significantly, and the coefficient of thermal expansion (CTE) is greater than 6 × 10⁻⁶. -6 / ℃.
[0021] 4) Composite divalent metal oxide RO, wherein the composite divalent metal oxide RO is composed of four oxides: ZnO, MgO, CaO, and SrO. The total molar content of RO is the sum of the four oxides, excluding BaO. Based on the total molar content of RO, MgO accounts for 40-60 mol%. MgO can optimize the short-range ordered structure of the glass, improving the coefficient of thermal expansion and fracture toughness. CaO and SrO fine-tune the network gaps. ZnO has excellent fluxing properties, effectively cutting off part of the silicon-oxygen network, reducing high-temperature viscosity, and improving the melting and forming performance of the high-alumina-silicon glass system of this invention. This effectively solves the process challenges brought about by the high-toughness formulation of this invention, promoting the realization of overflow, float, and slot-feed mass production processes. 2+It exhibits a certain electronic polarization effect under high-frequency conditions; adding it alone or in large quantities will lead to an increase in tanδ. Adding ZnO, followed by MgO, CaO, and SrO divalent metal oxides, can simultaneously address both thermal expansion and fracture toughness; the use of BaO and Ba is prohibited. 2+ High polarization characteristics lead to increased high-frequency losses in glass; RO greater than 12 mol% results in decreased thermal expansion coefficient and fracture toughness, while RO less than 6 mol% is unfavorable for melting. Furthermore, only a ZnO content of 0.5~1.0 mol% achieves optimal overall performance. The thermal expansion coefficient CTE is (4~6) × 10⁻⁶. -6 / ℃ range; 5) A composite rare earth oxide Re2O3, wherein Re2O3 contains Sc2O3, and one or two of Y2O3 and La2O3 selected from Sc 3+ The ionic radius of Y (approximately 0.75 Å) is much smaller than that of Y. 3+ (0.9 0 Å) and La 3+ (1.03 Å), Sc 3+ The ionic radius is the smallest, while the ionic radii of the other three exhibit a gradient change. Sc 3+ The ionic radius is even close to that of Mg. 2+ (0.72 Å). Therefore, it can more easily enter the gaps in the glass network, making the glass network structure more compact, improving the Si-O-Al bonding strength, and significantly increasing the fracture toughness to 1.5 MPa·m. 1 / 2 Additionally, Sc 3+ With its small ionic radius and high charge density, Sc's electron cloud is not easily deformed, resulting in extremely low polarizability. This is highly advantageous for maintaining ultra-low dielectric loss at 20 GHz, making it an essential material for this invention. Furthermore, like Y and La, Sc maintains a stable +3 valence in the glass melt, unlike Ce, Nd, and Pr, which undergo valence changes (electron transitions). Therefore, it does not introduce additional high-frequency polarization losses and does not worsen the dielectric loss at 20 GHz under room temperature (25°C).
[0022] 6) The composite trace additive RO2 includes ZrO2 and SnO2, with a total molar amount of 0.5~1.2 mol%, wherein the molar ratio of ZrO2 to SnO2 is 4:6~7:3. Both must be present simultaneously and cannot be added alone; Zr... 4+ High field strength of ions can suppress interfacial polarization, and a small amount of SnO2 and ZrO2 can suppress microcrystallization and enhance the strength of glass structure; the combination of the two reduces the probability of microcrack initiation and stabilizes the high-frequency dielectric constant and dielectric loss.
[0023] This invention provides a method for preparing an alkali-free oxide glass substrate for chip packaging, comprising the following steps: Step 1, Raw material pretreatment: Based on the composition of the glass substrate, select oxide or corresponding carbonate raw materials with a purity of ≥99.5%, convert them to mass ratios according to molar ratios, mix them evenly, and prepare the batch material. Step 2, High-temperature melting and clarification: The batch material is placed in a platinum container or a low-alkali refractory kiln with an alkali metal oxide content ≤0.1%, and kept at 1580~1650℃ for 6~8 h for melting and clarification; Step 3, Cooling and Homogenization: Cool the clarified glass melt to 1420-1480℃ and homogenize it by mechanical stirring for 1-3 hours; Step 4, Glass Forming: The homogenized molten glass is formed by overflow pull-down method, slit pull-down method, rolling method, float glass method or casting method to obtain glass substrate blanks or sheets with a thickness of less than 2.0 mm. Step 5, Annealing: The formed glass substrate blank or original sheet is annealed to 60~80℃ at a cooling rate of 10~350℃ / min to obtain an alkali-free oxide glass substrate for chip packaging.
[0024] This embodiment is based on the alkali-free oxide glass substrate formulation system. All embodiments do not contain alkali metal oxides, and the proportions of each component strictly follow the molar percentage range and oxide ratio constraints. The performance indicators are in line with the invention.
[0025] All components in the embodiments of this invention are measured using molar percentages, and performance is tested according to a unified standard. The coefficient of thermal expansion is measured using the push-rod method, with a test temperature range of 25–300°C; fracture toughness K… IC The three-point bending method using a single-sided V-shaped notched beam (SEVNB) was employed for testing; dielectric loss was tested using the 20 GHz cavity resonance method under room temperature conditions (25℃).
[0026] The specific implementation method is as follows: Example 1 The glass composition is as follows (see Table 1): SiO2 58 mol%, Al2O3 16 mol%, B2O3 15 mol%, MgO 3.6 mol%, ZnO 1.0 mol%, CaO 2.4 mol%, SrO 2.0 mol%, Sc2O3 0.5 mol%, Y2O3 1.0 mol%, ZrO2 0.3 mol%, SnO2 0.2 mol%, with each component totaling 100%. The total content of the composite divalent metal oxide RO is MgO (3.6 mol%) + CaO (2.4 mol%) + SrO (2 mol%) + ZnO (1.0 mol%) = 9 mol%, of which MgO accounts for 3.6 / 9 = 40% of the total RO molarity, which meets the requirement of "MgO accounting for 40%~60% of the total RO molarity".
[0027] The glass performance test results are: CTE = 4.6 × 10⁻⁶ -6 / ℃, K IC =1.4 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0036.
[0028] Example 2 The glass composition is as follows (see Table 1): SiO2 64 mol%, Al2O3 14.8 mol%, B2O3 11 mol%, MgO 3.3 mol%, ZnO 0.7 mol%, CaO 1.0 mol%, SrO 1.0 mol%, Sc2O3 0.2 mol%, La2O3 3 mol%, ZrO2 0.4 mol%, SnO2 0.6 mol%, with a total of 100% for all components.
[0029] The glass performance test result is: CTE = 4.0 × 10⁻⁶ -6 / ℃, K IC =1.4 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0039.
[0030] Example 3 The glass composition is as follows (see Table 1): SiO2 65 mol%, Al2O3 14 mol%, B2O3 8 mol%, MgO 4 mol%, ZnO 0.5 mol%, CaO 1.5 mol%, SrO 1.5 mol%, Sc2O3 0.3 mol%, Y2O3 2.5 mol%, La2O3 1.7 mol%, ZrO2 0.7 mol%, SnO2 0.3 mol%, with a total of 100% for all components.
[0031] The glass performance test results are: CTE = 4.8 × 10⁻⁶ -6 / ℃, K IC =1.5 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0042.
[0032] Example 4 The glass composition is as follows (see Table 1): SiO2 60.0 mol%, Al2O3 13.3 mol%, B2O3 12.5 mol%, MgO 5.2 mol%, ZnO 1.3 mol%, CaO 2.0 mol%, SrO 2.0 mol%, Sc2O3 0.4 mol%, La2O3 2.8 mol%, ZrO2 0.3 mol%, SnO2 0.2 mol%, with a total of 100% for all components.
[0033] The glass performance test result is: CTE = 5.3 × 10⁻⁶-6 / ℃, K IC =1.4 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0040.
[0034] Example 5 The glass composition is as follows (see Table 1): SiO2 61 mol%, Al2O3 12 mol%, B2O3 10.8 mol%, MgO 7.2 mol%, ZnO 1.5 mol%, CaO 1.5 mol%, SrO 1.8 mol%, Sc2O3 0.2 mol%, Y2O3 2.8 mol%, ZrO2 0.7 mol%, SnO2 0.5 mol%, with a total of 100% for all components.
[0035] The glass performance test result is: CTE = 6.0 × 10⁻⁶ -6 / ℃, K IC =1.5 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0045.
[0036] Example 6 The glass composition is as follows (see Table 1): SiO2 55 mol%, Al2O3 18 mol%, B2O3 13.5 mol%, MgO 4.5 mol%, ZnO 1.8 mol%, CaO 1.7 mol%, SrO 1.0 mol%, Sc2O3 0.1 mol%, Y2O3 1.9 mol%, La2O3 1.5 mol%, ZrO2 0.5 mol%, SnO2 0.5 mol%, with a total of 100% for all components.
[0037] The glass performance test result is: CTE = 5.7 × 10⁻⁶ -6 / ℃, K IC =1.2 MPa·m 1 / 2 , 20GHz@25℃ tanδ=0.0044.
[0038] It should be noted that the preparation methods of the glass substrates in Examples 1 to 6 above all follow steps 1 to 6. The selection of specific process parameters in the melting and clarifying process in step 2, the cooling and homogenization process in step 3, and the annealing process in step 5 is based on the conventional selection of adaptability to different glass forming processes. It does not directly affect the test performance of the glass's coefficient of thermal expansion, fracture toughness, and dielectric loss.
[0039] Comparative Example 1 Comparative Example 1 is alkali-free display glass, i.e., mainstream LCD substrate glass. Its composition (mol%) is: SiO2 66.1%, Al2O3 12.3%, B2O3 9.5%, MgO 2.5%, CaO 9.0%, SrO 0.6 mol%, excluding ZnO / Sc / Zr / Sn. Performance testing was conducted according to the method described in the specific implementation plan: CTE = 3.3 × 10⁻⁶. -6 / ℃, KIC=1.1 MPa·m 1 / 2 tanδ=0.0053. This indicates that the CTE is too low and mismatched with silicon; K IC Both tanδ and tanδ are inferior to the present invention.
[0040] Comparative Example 2 Comparative Example 2 is a cover glass containing Na₂O, i.e., mobile phone screen protection glass. Its composition (mol%) is: SiO₂ 67.7, Al₂O₃ 12.2, B₂O₃ 4.2, MgO 2.4, Na₂O 13.5 mol%. Performance: CTE = 7.8 × 10⁻⁶ -6 / ℃, K IC =0.7 MPa·m 1 / 2 The tanδ value is 0.0284. It contains alkali metal oxides, has excessively high CTE, and severely exceeds the tanδ limit, making it completely unsuitable for high-end semiconductor packaging.
[0041] Comparative Example 3 Comparative Example 3 is an OLED display substrate glass. Although it contains La₂O₃, Y₂O₃, SnO₂, and ZrO₂, it lacks Sc₂O₃ and ZnO. Its composition (mol%) is: SiO₂ 69.5, Al₂O₃ 13.7, B₂O₃ 1.7, MgO 4.5, CaO 5.6, SrO 1.2, La₂O₃ 2.1, Y₂O₃ 1.4, SnO₂ 0.3, ZrO₂ 1.4 mol%. Performance: CTE = 3.5 × 10⁻⁶ -6 / ℃, K IC =1.0 MPa·m 1 / 2 tanδ=0.0062. Although it contains Y2O3 / La2O3 and ZrO2 / SnO2, the three indicators failed to meet the standards in a coordinated manner due to the lack of Sc2O3 and ZnO.
[0042] Comparative Example 4 Comparative Example 4 is a control glass without Sc2O3. Its composition (mol%) is: SiO2 65.0, Al2O3 14.0, B2O3 8.0, MgO 4.0, ZnO 0.5, CaO 1.5, SrO 1.5, Y2O3 2.8, La2O3 1.7, ZrO2 0.7, SnO2 0.3 mol%. Performance: CTE = 3.7 × 10⁻⁶-6 / ℃, K IC =1.1 MPa·m 1 / 2 tanδ=0.0064. After removing Sc2O3, K IC Both tanδ and Sc2O3 show deterioration, proving that Sc2O3 is an essential reinforcing and low-polarity component.
[0043] Comparative Example 5 Comparative Example 5 is a control glass without ZnO. Its composition (mol%) is: SiO₂ 60.0, Al₂O₃ 13.3, B₂O₃ 12.5, MgO 5.2, CaO 3.3, SrO 2.0, Sc₂O₃ 0.4, La₂O₃ 2.8, ZrO₂ 0.3, SnO₂ 0.2 mol%. Performance: CTE = 3.5 × 10⁻⁶ -6 / ℃, K IC =1.1 MPa·m 1 / 2 The tanδ = 0.0059, but with a 50°C increase in melting and homogenization temperature, bubbles and streaks increase by more than 20% during the molding process, resulting in a decrease in product quality. This proves that ZnO is the key fluxing component for achieving the manufacturing process of this invention.
[0044] Comparative Example 6 Comparative Example 6 is a control glass containing only SnO2 and no ZrO2, otherwise identical to Comparative Example 5. Its composition (mol%) is: SiO2 60.0, Al2O3 13.3, B2O3 12.5, MgO 5.2, CaO 3.3, SrO 2.0, Sc2O3 0.4, La2O3 2.8, SnO2 0.5 mol%. Performance: CTE = 3.6 × 10⁻⁶ -6 / ℃, K IC =1.0 MPa·m 1 / 2 The tanδ = 0.0057, and the glass is prone to slight devitrification after annealing (SnO2 microcrystalization). This example proves that ZrO2 and SnO2 must be used in combination; using SnO2 alone will induce glass crystallization.
[0045] Analysis of the above comparative examples fully demonstrates the advantages of this invention in terms of excellent low brittleness, high toughness, and low dielectric loss. In addition, it also has the advantage of packaging that matches the chip expansion coefficient.
[0046] The glass composition ratios and performance tests of Examples 1-6 are shown in Table 1.
[0047] Table 1 The glass composition ratios and performance tests of Comparative Examples 1 to 6 are shown in Table 2.
[0048] Table 2 The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An alkali-free oxide glass substrate for chip packaging, characterized in that, The glass substrate is completely free of alkali metal oxides Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O, and also free of BaO and variable-valence rare earth oxides Ce₂O₃, Nd₂O₃, and Pr₂O₃; the total amount of each component is 100% by mole percentage, and it consists of the following components: SiO2 55.0~65.0 mol% Al2O3 12.0~18.0 mol% B2O3 8.0~15.0 mol% Complex divalent metal oxides RO 6.0–12.0 mol% Rare earth modified oxide Re2O3 1.5~4.5 mol% Composite trace additive RO2 0.5~1.2 mol%; in: The composite divalent metal oxide RO is composed of MgO, ZnO, CaO, and SrO, with MgO accounting for 40% to 60% of the total molar amount of RO. The rare earth modified oxide Re2O3 contains Sc2O3, and also contains at least one of Y2O3 and La2O3, wherein 0.1 mol% ≤ Sc2O3 ≤ 0.5 mol%, Y2O3 ≤ 2.8 mol%, and La2O3 ≤ 3.0 mol%; The composite trace additive RO2 contains both ZrO2 and SnO2, with a molar ratio of 4:6 to 7:
3.
2. The glass substrate according to claim 1, characterized in that, The content of each component, expressed as a molar percentage, is as follows: SiO2 58.0~62.0 mol% Al2O3 14.0~16.0 mol% B2O3 10.0~13.0 mol% RO 8.0~10.0 mol% Re₂O₃ 2.5–3.5 mol% RO2 0.5~1.0 mol%.
3. The glass substrate according to claim 1 or 2, characterized in that, The content of each component in the RO meets the following requirements: MgO 3.3-7.2 mol%, ZnO 0.5-1.8 mol%, CaO 1.0-2.4 mol%, SrO 1.0-2.0 mol%; and the molar ratio of ZnO to MgO is 0.13-0.
25.
4. The glass substrate according to claim 1 or 2, characterized in that, The molar ratio of Sc2O3 to (Y2O3+La2O3) in the Re2O3 is (0.03~0.50):
1.
5. The glass substrate according to claim 1 or 2, characterized in that, In the composite trace additive RO2, ZrO2 is 0.3-0.7 mol% and SnO2 is 0.2-0.6 mol%.
6. A method for preparing a glass substrate according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1, Raw material pretreatment: Based on the composition of the glass substrate, select oxide or corresponding carbonate raw materials with a purity of ≥99.5%, convert them to mass ratios according to molar ratios, mix them evenly, and prepare the batch material. Step 2, High-temperature melting and clarification: The batch material is placed in a platinum container or a low-alkali refractory kiln with an alkali metal oxide content ≤0.1%, and kept at 1580~1650℃ for 6~8 h for melting and clarification; Step 3, Cooling and Homogenization: Cool the clarified glass melt to 1420-1480℃ and homogenize it by mechanical stirring for 1-3 hours; Step 4, Glass Forming: The homogenized molten glass is formed by overflow pull-down method, slit pull-down method, rolling method, float glass method or casting method to obtain glass substrate blanks or sheets with a thickness of less than 2.0 mm. Step 5, Annealing: The formed glass substrate blank or original sheet is annealed to 60~80℃ at a cooling rate of 10~350 ℃ / min to obtain an alkali-free oxide glass substrate for chip packaging.
7. The application of a glass substrate according to any one of claims 1 to 5 or a glass substrate prepared by the preparation method according to claim 6, characterized in that, The glass substrate is used in any one of the following: high-performance AI chip packaging substrate, high-bandwidth memory interposer, 6G millimeter-wave RF chip packaging substrate, co-packaged optical glass interposer, glass through-hole vertical interconnect substrate, and glass-based fan-out packaging substrate.